ALTERNATIF PENGOLAHAN LIMBAH RUMAH POTONG HEWAN - CAKUNG ( SUATU STUDI KASUS ) - Djoko Padmono (Jurnal Teknologi Lingkungan, 2005)
Public awareness on environmental protection is getting better now. This condition has also rise in a company own by Province Governmental of DKI Jakarta Raya in the field of slaughtering cattle. This company, namely Cakung Slaughterhouse stay in Jakarta Timur is more a public services instead of a private company. On the waste and wastewater handling as the by product of all activity in Cakung Slaughterhouse, an assessment and development of handling waste and wastewater was carried outcooperation with German agricultural research institute (Bundesforschunganstaltfuerlandwirschaft – FAL) through on the job training, design and engineering of the waste and wastewater treatment plant that would be developed. The training was done by handling the waste of German slaughterhouse as a case study in Germany that has no experience in it on a Cooperation Project of Biological Waste and Wastewater treatment – BTIG Project. Fortunately, beside the technologyand system on waste and wastewater handling, also getting the high awareness in condition for a healthy circumference of life need. Make this project as basic of design on waste and wastewater treatment plant of a slaughterhouse, at least on the essentials organic waste treatment mode.